A safe fracture fatigue life prediction based on equivalent initial flaw size. (January 2021) - Li, Fei; Wen, Zhixun; Wu, Ziyan; Liu, Shuangbo; Li, Zhenwei; Pei, Haiqing; Yue, Zhufeng
Highlights: Fatigue crack growth data at five different temperatures. Total fatigue life prediction based on equivalent initial flaw size. Modified Kitagawa-Takahashi diagram method. Maximum likelihood estimation. Probability expression of safe fatigue fracture life. Abstract: The equivalent initial flaw size (EIFS) concept was developed to provide an initial damage state for fracture mechanics-based life prediction. This study focuses on the safe fracture fatigue life prediction based on EIFS concept. A novel assessment method (M-K-T), the maximum likelihood estimation (MLE) method updated by modified Kitagawa-Takahashi (K-T) diagram method, is proposed to obtain general EIFS distribution and further predict the total fatigue life. The accuracy of the prediction method is proved by the fatigue crack propagation test of Ti2 AlNb-based alloy under five different temperature (R.T., 200 °C, 400 °C, 500 °C, and 600 °C). Based on total fatigue life and uncertain damage mapping, the probability function of safe fracture fatigue life is derived considering the errors of experimental measurement and theoretical derivation.